THEMATIC SIMILARITIES OF ENGLISH AND UZBEK PROVERBS - Rakhimova, Durdona Norimovna; Yugay , Evgeniya Viktorovna (INTERNATIONAL CONFERENCE DEDICATED TO THE ROLE AND IMPORTANCE OF INNOVATIVE EDUCATION IN THE 21ST CENTURY, 2022)
Proverbs are one of the genres of concise, profound oral creation, based on the experience and observations of the people over the centuries in socio-economic, political and cultural life. This article discusses thematic similarities of English and Uzbek proverbs.